2022
DOI: 10.3390/brainsci12081025
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cerebral Hemodynamic Monitoring during Carotid Endarterectomy via Diffuse Correlation Spectroscopy and Near-Infrared Spectroscopy

Abstract: Objective: This pilot study aims to show the feasibility of noninvasive and real-time cerebral hemodynamic monitoring during carotid endarterectomy (CEA) via diffuse correlation spectroscopy (DCS) and near-infrared spectroscopy (NIRS). Methods: Cerebral blood flow index (CBFi) was measured unilaterally in seven patients and bilaterally in seventeen patients via DCS. In fourteen patients, hemoglobin oxygenation changes were measured bilaterally and simultaneously via NIRS. Cerebral autoregulation (CAR) and cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The latter proved to be feasible, as highlighted by the absence of protocol violations, and resulted in a clear biological effect indicated by significantly different arterial blood pressures and norepinephrine dosages between the two groups. Although other neuromonitoring tools have been used to detect cerebral hypoperfusion during CEA [14,29,30], we used a NIRS-guided protocol because NIRS is a validated and widely available neuromonitoring technique, easy to use, and can be interpreted without specific training in neurophysiology [6,[14][15][16][17]31]. A systematic review and meta-analysis concluded that NIRS has a low sensitivity, but high specificity to identify intraoperative ischemia compared with awake monitoring in patients undergoing CEA [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter proved to be feasible, as highlighted by the absence of protocol violations, and resulted in a clear biological effect indicated by significantly different arterial blood pressures and norepinephrine dosages between the two groups. Although other neuromonitoring tools have been used to detect cerebral hypoperfusion during CEA [14,29,30], we used a NIRS-guided protocol because NIRS is a validated and widely available neuromonitoring technique, easy to use, and can be interpreted without specific training in neurophysiology [6,[14][15][16][17]31]. A systematic review and meta-analysis concluded that NIRS has a low sensitivity, but high specificity to identify intraoperative ischemia compared with awake monitoring in patients undergoing CEA [32].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate arterial blood pressure control is a key risk factor for the development of brain ischemia, myocardial complications, and perioperative death in patients undergoing CEA [5]. Studies show that increasing arterial blood pressure during carotid cross-clamping can improve cerebral oxygenation [6] and prevent or reverse perioperative neurological deficits [7]. Experts recommend either tolerating arterial hypertension or increasing arterial blood pressure ≥ 20% over baseline values during carotid cross-clamping [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, diffuse correlation spectroscopy (DCS), a diffuse optical technique used to estimate microvascular perfusion 10 , allows for a non-invasive, continuous estimate of blood flow in the brain. DCS has been validated against several gold-standard perfusion monitoring techniques including arterial spin labeled MRI 11,12 , Xenon-CT 13 , positron emission tomography 14 , and tracer bolus tracking 15 , and has been used extensively in research to assess CBF in multiple clinical scenarios, including major cardiac surgeries [16][17][18][19] and longterm monitoring of acute brain injury in the neuro ICU 13,[20][21][22] . Traditionally, DCS has been performed using continuous wave illumination, which, due to the partial volume effect, intrinsically links the measurement source-detector separation (SDS), cerebral sensitivity, and signal-to-noise ratio of the measurement 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Through the measurement of diffusely backscattered light, DCS relates the temporal fluctuations of the collected signals to the motion of blood cells through the vasculature. Bedside clinical blood flow monitoring 2 , especially cerebral blood flow monitoring 3 , has exploded as a use case for DCS, with DCS having been used to estimate metrics of cerebral perfusion during surgical procedures 4 8 , cerebral autoregulation 9 , 10 , cerebrovascular reactivity 11 , intracranial pressure 12 14 , and critical closing pressure 15 , 16 . While a number of studies including DCS monitoring have been demonstrated in adult populations, due to limitations in cerebral sensitivity and signal-to-noise ratio 17 , the standard DCS technique is better suited to measure blood flow in neonates and children, where the extracerebral tissue (scalp and skull) is significantly thinner than in adults 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%